COMMUNICATIVE STYLES IN THE NOVEL “SANG ETNOGRAF” - Satriani Satriani (Elite : English and Literature Journal, 2021)
The research is about the study of communication style based on the reader’ perspectif on novel “Sang Etnograf” by Murni Mahmud. the researchers tried to investigate the communication strategies of the performers in textual dialogues of a novel which includes linguistic form and some cultural aspects in Bugis society.The findings of this study are there are five extract based on the kinds of speech act production , there are four extract about discourse markers , there are three extract about the language choices, there are five extract about the address terms and the last is about the regional term consists of three extract is about ergative pronoun, exclusive and inclusive.This research was successful in making an attempt of determining communicative styles used by the several characters in the dialogue of novel of “Sang Etnograf”. This research have presented some extract which talks about some aspect of communication styles such as the speech act production, discourse marker, address term, language choice and regional term.